%! TEX root = LST.tex % vim: tw=50 % 17/02/2024 09AM \begin{flashcard}[proof-first-order-defn] \begin{definition*}[Proof (in first-order logic)] \glssymboldefn{ssynentails}{$\vdash$}{$\vdash$} \glsnoundefn{fproof}{proof}{proofs} \cloze{Let $S$ be a set of \glspl{form}, and $p$ a \gls{form}. A \emph{proof of $p$ from $S$} is a finite sequence $t_1, \ldots, t_n$ of \glspl{form} such that $t_n = p$ and for every $i$, we have one of: \begin{itemize} \item $t_i \in S$ or $t_i$ is an axiom. \item $\exists j, k < i$ with $t_k = (t_j \pimpl t_i)$. \item $\exists j < i$ with $t_i = (\pforall x) t_j$, $x \in \FV(t_j)$ and for all $k < j$ if $t_k \in S$ then $x$ does not occur \gls{free} in $t_k$. \end{itemize} In this case we say \emph{$S$ proves $p$} and write $S \vdash p$. (If $S$ is a \gls{theory} and $p$ is a \gls{sent} then we say \emph{$p$ is a theorem of $S$}).} \end{definition*} \end{flashcard} \begin{remark*} Suppose we allow $\emptyset$ as a structure. Note that $(\pforall x)\pnot (x = x)$ is satisfied in $\emptyset$, whereas $\false$ is not. So $\{(\pforall x)\pnot (x = x)\} \not \ssementails \false$. However, $\{(\pforall x)\pnot(x =x)\} \ssynentails$: \begin{align*} &(\pforall x)\pnot (x = x) &&\text{(premise)} \\ &((\pforall x)\pnot(x =x)) \pimpl (\pnot(x = x)) &&\text{(A6)} \\ &\pnot (x = x) &&\text{(\gls{MP})} \\ &(\pforall x)(x = x) &&\text{(A4)} \\ &(x = x) &&\text{(A6 + \gls{MP})} \\ &\false &&\text{(\gls{MP})} \end{align*} \end{remark*} \begin{example*} $\{x = y\} \ssynentails (y = x)$. \begin{align*} &(\pforall x)(\pforall y)((x = y) \pimpl ((x = z) \pimpl (y = z)) &&\text{(A5)} \\ &(x = y) \pimpl ((x = z) \pimpl (y = z)) &&\text{((A6 + \gls{MP}) twice)} \\ &x = y &&\text{(premise)} \\ &(x = z) \pimpl (y = z) &&\text{(\gls{MP})} \\ &(\pforall z)((x = z) \pimpl (y = z)) &&\text{(Gen)} \\ &((\pforall z)((x = z) \pimpl (y = z))) \pimpl ((x = x) \pimpl (y = z)) &&\text{(A6)} \\ &(x = x) \pimpl (y = x) &&\text{(\gls{MP})} \\ &(\pforall x)(x = x) &&\text{(A4)} \\ &(x = x) &&\text{(A6 + \gls{MP})} \\ &(y = x) &&\text{(\gls{MP})} \end{align*} \end{example*} \begin{flashcard}[first-order-deduction-thm] \prompt{(In first order logic)} \begin{proposition}[Deduction Theorem] \label{fo_ded_thm} \cloze{Let $S$ be a set of \glspl{form} and $p, q$ be \glspl{form}. Then $S \ssynentails (p \pimpl q)$ if and only if $S \cup \{p\} \ssynentails q$.} \end{proposition} \begin{proof} \phantom{} \cloze{\begin{enumerate}[$\Rightarrow$] \item[$\Rightarrow$] Write down a \gls{fproof} of $p \pimpl q$ from $S$ and add the lines: \begin{align*} &p &&\text{(premise)} \\ &q &&\text{(\gls{MP})} \end{align*} to get a \gls{fproof} of $q$ from $S \cup \{p\}$. \item[$\Leftarrow$] Let $t_1, \ldots, t_n = q$ be a proof of $q$ from $S \cup \{p\}$. We proe $S \ssynentails (p \pimpl t_i)$ by induction on $i$. Our induction hypothesis at step $i$ will be: for $j < i$, $S \ssynentails (p \pimpl t_j)$ such that if the \gls{fproof} of $t_j$ from $S \cup \{p\}$ did not use any premise in which a \gls{var} $x$ occurs \gls{free}, then the \gls{fproof} of $(p \pimpl t_j)$ from $S$ does not use any premise in which a \gls{var} $x$ occurs \gls{free}. To see $S \ssynentails (p \pimpl t_i)$, we consider cases: \begin{itemize} \item If $t_i \in S$ or $t_i$ an axiom, write \begin{align*} &t_i &&\text{(premise or axiom)} \\ &t_i \pimpl (p \pimpl t_i) &&\text{(A1)} \\ &p \pimpl t_i &&\text{(\gls{MP})} \end{align*} is a \gls{fproof} of $(p \pimpl t_i)$ from $S$. \item If $t_i = p$, then write down a proof of $p \pimpl p$ from $\emptyset$. \item If $\exists j, k < i$ with $t_k = (t_j \pimpl t_i)$ then write \begin{align*} &(p \pimpl (t_j \pimpl t_i)) \pimpl ((p \pimpl t_j) \pimpl (p \pimpl t_i)) &&\text{(A2)} \\ &p \pimpl (t_j \pimpl t_i) &&\text{(by induction hypothesis)} \\ &(p \pimpl t_j) \pimpl (p \pimpl t_i) &&\text{(\gls{MP})} \\ &p \pimpl t_j &&\text{(by induction hypothesis)} \\ &p \pimpl t_i &&\text{(\gls{MP})} \end{align*} \item Finally, if $\exists j < i$ such that $x \in \FV(t_j)$ and $t_i = (\pforall x) t_j$, then the \gls{fproof} of $t_j$ from $S \cup \{p\}$ did not use any premise in which $x$ occurs \gls{free}. If $x$ occurs \gls{free} in $p$, then $p$ did not occur in proof of $t_j$ from $S \cup \{p\}$, i.e. it is a proof of $t_j$ from $S$. By (Gen), $S \ssynentails (\pforall x) t_j$, i.e. $S \ssynentails (\pforall x) t_j$, i.e. $S \ssynentails t_i$. Add the lines \begin{align*} &t_i \pimpl (p \pimpl t_i) &&\text{(A1)} \\ &p \pimpl t_i &&\text{(\gls{MP})} \end{align*} If $x$ does not occur \gls{free} in $p$, then we have a \gls{fproof} of $p \pimpl t_j$ from $S$ by induction hypothesis, which does not use any premise in which $x$ occurs \gls{free}. So we can add: \begin{align*} &(\pforall x)(p \pimpl t_j) &&\text{(Gen)} \\ &((\pforall x)(p \pimpl t_j)) \pimpl (p \pimpl (\pforall x) t_j) &&\text{(A7)} \\ &\ub{p \pimpl (\pforall x) t_j}_{= p \pimpl t_i} &&\text{(\gls{MP})} \end{align*} \end{itemize} In all cases the condition about \gls{free} \glspl{var} remains true. \qedhere \end{enumerate}} \end{proof} \end{flashcard} \textbf{Aim:} $S \ssynentails p$ if and only if $S \ssementails p$. \begin{flashcard}[soundness-first-order-thm] \prompt{(In first-order logic)} \begin{proposition}[Soundness Theorem] \label{fo_soundness} \cloze{Let $S$ be a set of \glspl{form} and $p$ be a \gls{form}. If $S \ssynentails p$ then $S \fsementails p$.} \end{proposition} \begin{proof}[Proof (non-examinable)] \cloze{Write down a proof $t_1, \ldots, t_n$ of $p$ from $S$. Verify thet $S \fsementails t_i$ by an easy induction.} \end{proof} \end{flashcard} \begin{flashcard}[model-existence-first-order-thm] \begin{theorem}[Model Existence Lemma] \label{fo_model_existence} \cloze{Let $S$ be a \gls{cons} \gls{theory} in the \gls{folang} $L = L(\pOmega, \pPi, \arity)$ (i.e. $S \not\ssynentails \false$). Then $S$ has a \gls{fmodel}.} \end{theorem} \end{flashcard} Assuming this, we have: \begin{flashcard}[adequacy-first-order-thm] \begin{corollary}[Adequacy Theorem] \cloze{Let $S$ be a set of \glspl{form} and $p$ be a \gls{form}. If $S \fsementails p$, ten $S \fsementails p$.} \end{corollary} \begin{proof}[Proof (non-examinable)] \cloze{Without loss of generality $S$ is a \gls{theory} and $p$ is a \gls{sent} (by using the definition of $\fsementails$ in the case where we have \glspl{form} rather than \glspl{sent}). Since $S \ssementails p$, $S \cup \{\pnot p\} \ssementails \false$. So by \cref{fo_model_existence}, $S \cup \{\pnot p\} \ssynentails \false$. So $S \ssynentails \pnot \pnot p$ (by \cref{fo_ded_thm}), so $S \ssynentails p$ by (A3) and (\gls{MP}).} \end{proof} \end{flashcard} \begin{flashcard}[godel-completeness-first-order-thm] \begin{theorem}[G\"odel's Completeness Theorem for first-order logic] \cloze{If $S$ is a set of \glspl{form} and $p$ is a \gls{form}, then $S \ssynentails p$ if and only if $S \fsementails p$.} \end{theorem} \end{flashcard} \glsadjdefn{closed}{closed}{\gls{term}} \textbf{Idea of proof of \cref{fo_model_existence}:} We build a \gls{fmodel} from $L = L(\pOmega, \pPi)$. Let $A$ be the set of \emph{closed} \glspl{term} in $L$, i.e. \glspl{term} with no \glspl{var}. For example $S = \text{\gls{theory} of fields}$ (in \gls{folang} of commutative rings with $1$). $A$ consists of \[ 1 + 1, (((1 + 0) + 0) + 1), 1 \cdot 1, 1 \cdot 0, \ldots, 1 + (-1), \ldots \] We will define the \gls{interpf} of $+$ (and other symbols similarly) using: \[ (1 + 1) +_A (1 + 0) = (1 + 1) + (1 + 0) \]